P130 Adhesions are not always the enemy: pouch volvulus. (27th May 2021) - Dionigi, B; Lavaryk, O; Lightner, A; Holubar, S; Hull, T
Abstract: Background: Proctocolectomy with ileal pouch anal anastomosis (IPAA) was introduced over 40 years ago, prior to the era of laparoscopy. Minimally invasive surgery (MIS) techniques have been applied to pelvic pouch surgery. One advantage of MIS is the reduction in adhesion-related complications. The lack of adhesions may result in different complications. When the pouch is not adherent in the pelvis, pouch volvulus can occur around the mesenteric axis. The aim of this study was to describe our experience with pelvic pouch volvulus. Methods: Our prospectively maintained pelvic pouch registry and our enterprise wide electronic medical record were queried for keyword combinations of "pouch volvulus" between 1994 and 2020. Pouch volvulus was defined as torsion of the ileal pouch on its mesenteric axis or around small bowel maintaining the proper orientation of the ileo-anal anastomosis. Patients with pouches constructed with twisted mesenteric axis from ill-aligned anastomoses were excluded. Data for these patients was collected from the pouch registry and additional chart review. Results: We identified 17 patients with pouch volvulus; of these, 11 patients did not meet our selection criteria and were excluded. Of the 6 patients (5 female; median age 25) with true volvulus, the diagnosis at IPAA was ulcerative colitis (n=5) and Lynch syndrome with a rectal cancer. All pelvic pouches were constructed with MIS techniques, including standard laparoscopy (n=4) and single incision laparoscopic technique (n=2). All 6 patients presented with diffuse abdominal pain and abdominal distention. The average time from pouch construction to pouch volvulus was 2.5 years (range: 5.2 – 97.5 months). Computed tomography with or without rectal contrast was the initial diagnostic test in 4/6 with findings highly suspicious for pouch volvulus. Surgery was performed urgently in 5/6 of patients; all 6 had open surgery. At reoperation, all had minimal adhesions and a gap between the pouch mesentery and the retroperitoneum. Interventions included pouch-pexy (n=3), closure of gap between pouch and sacrum (n=2), and pouch excision and ileostomy (n=1). At a median of 9 months (IQR: 4–97) of follow up, pouch survival was 83%; functional outcomes included mild fecal incontinence (n=1) and paradox requiring intermittent pouch intubation for stool evacuation (n=1). Conclusion: Pelvic pouches constructed by minimally invasive techniques may be at risk for pouch volvulus due to minimal adhesions. Surgeons should have a high index of suspicion for patients with unexplained abdominal pain, distension, and other obstructive symptoms. Cross-sectional imaging with rectal contrast, may help clarify the diagnosis. Immediate surgical care can allow for pouch salvage.